Effect of Root-Up Concentration and Planting Media on Crown Root Formation in Pineapple Plants (Ananas comosus L. Merr) Smooth Cayenne - Arga, Arga; Sondari, Nunung; Parlinah, Linlin (Agripreneur : Jurnal Pertanian Agribisnis, 2023)
This research was carried out from September to November 2022 at an altitude of 447.0 m above sea level, Cirangkong Village, Cijambe District, Subang Regency, West Java Province. This study is to study the growth of crown roots in pineapple plants with the application of Root UP and different planting media. Therefore, the research method used is verification by conducting field experiments using polybags. The materials used in this experiment were Smooth Cayenne Pineapple crown seeds, Root-UP, planting media (soil and husks), polybags and water. Meanwhile, the tools used in this experiment are meters, hoes, electric scales, buckets, dippers, calculators, stationery and cameras. This experiment was carried out using a Random Group Design (RAK) of a factorial pattern consisting of two factors, the first factor was the concentration of Root-UP (H) of 4 levels and the second factor was the planting medium (M) of 4 levels, repeated 3 times. There were 16 treatment combinations that were randomly placed on each replicate. The results showed that the treatment of Root-UP concentration and planting medium had a significant effect on the number of crown roots, crown root length, and crown root dry weight in pineapple plants of the Smooth Cayenne variety. The use of Root-UP Concentration (3.5 mg L-1) had a significant effect on crown root length, and did not differ significantly on the dry weight of crown roots in Smooth Cayenne pineapple plants. Planting medium (Soil Media + Husk 1 : 1) has a real effect on the number of crown roots, crown root length and crown dry weight in pineapple plants of the Smooth Cayenne variety